Balancing Religious Freedom and Family Protection: Constitutional Issues of Interfaith Marriage in Indonesia from a Maqasid al-Usrah Perspective - Usman, Usman; Sayehu, Sayehu; Aspandi, Aspandi (Al Ahkam, 2026)
This research was motivated by the juridical problem of interfaith marriage in Indonesia. This problem includes the guarantee of the dimension of family goals. This study aims to analyze the guarantee of the dimension of family goals in the constitution of the Indonesian Marriage Law for perpetrators of interfaith marriages. Methodologically, this research is normative juridical research with a qualitative approach to the concept of family goals (maqasid al-usrah) as an analytical perspective. The data analyzed include the Constitution of the Marriage Law Number 16 of 2019, journal articles, books, and other literature related to the discussion. The results of this study indicate that the Indonesian Marriage Law has not guaranteed the dimension of family goals for interfaith marriage practitioners in Indonesia. This study's implications emphasize that family goals (maqasid al-usrah) can serve as a basis for addressing the juridical problem of interfaith marriage in Indonesia. The contextualization of the Marriage Law's constitution in the form of articles that guarantee the dimensions of family goals for perpetrators of interfaith marriage in Indonesia is necessary.